Evaluation of Wireless Network Security with Penetration Testing Method at PT PLN UP2D S2JB - Ariyadi, Tamsir; Irham, Irham; Cahyadi, Eko Fajar (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Advances in information and communication technology continue to develop over time. This causes significant changes in social, economic, and political conditions. One of the companies that require strong network security is PT. PLN (Perusahaan Listrik Negara) Persero which is the leading energy company in Indonesia. In this case, the a need to evaluate network security at PT. PLN becomes very important. This evaluation will help identify vulnerabilities and security gaps that exist in PT. PLN's network infrastructure. Network security evaluation using the penetration testing execution standards (PTES) method can provide an overview of the vulnerabilities or weaknesses of the network system at PT. PLN UP2D S2JB which has quite a lot of gaps to be exploited. The parameters used in this study are attacking the infrastructure, The rogue access point, and ARP Spoofing to test the wireless network security system. This is evidenced by the results of the 15 tests carried out, only two failed, namely in the type of attack on the rogue access point. The results of penetration testing are very necessary and important as feedback for system managers in fixing existing vulnerabilities.